Struktur Dan Fungsi Sosial Cerita Rakyat Legenda Batu Manangih Masyarakat Kenagarian Balai Panjang Kecamatan Lareh Sago Halaban Kabupaten Limapuluh Kota - Anggik Pradana; Zulfadhli (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This article describes the structure of the folklore of the legend of Batu Manangih, Balai Panjang Village, Lareh Sago Halaban District, Limapuluh Kota Regency, and the social function of the Batu Manangih legend folklore, Balai Panjang Village, Lareh Sago Halaban District, Limapuluh Kota Regency. This study used a qualitative approach using descriptive data originating from the folklore of the Batu Manangih legend, Balai Panjang Village, Lareh Sago Halaban District, Limapuluh Kota Regency, which was collected through two stages. In the first stage of recording the legend of Batu Manangih folklore. In the second stage, after recording the folklore, after that, collecting data on the storytelling environment using recording, observation and interview techniques. To analyze the data, it was carried out in four stages: (1) matching data with transcription and transliteration of data (2) analyzing data (3) discussing data analysis (4) reporting. This research produced, first, the structure of the folklore legend of Batu Manangih, Balai Panjang Village, Lareh Sago Halaban District, Limapuluh Kota Regency, namely, (a) style of language (b) characters and characterizations (c) setting (d) plot (e) theme (f ) mandate. The second is the social function of folklore, the legend of Batu Manangih, the Kenagarian community, Balai Panjang, Lareh Sago Halaban District, Limapuluh Kota Regency, namely, (a) educating (b) passing on (c) identity. The second is the social function of the legend of Batu Manangih, Balai Panjang Village, Lareh Sago Halaban District, Limapuluh Kota Regency, namely, (a) educating (b) passing on (c) identity